2011
DOI: 10.1002/dneu.20895
|View full text |Cite
|
Sign up to set email alerts
|

The role of Pax6 in forebrain development

Abstract: Pax6 encodes a highly conserved transcriptional regulator with two DNA-binding motifs, a paired domain and a paired-like homeodomain. Humans carrying PAX6 loss-of-function mutations suffer from abnormal development of the eyes (congenital aniridia) and brain. Small eye mice carrying Pax6 loss-of-function mutations provide a good model for these human conditions. Their analysis has demonstrated the critical importance of this transcription factor in multiple cell types and at several key stages of forebrain dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
137
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(146 citation statements)
references
References 155 publications
6
137
0
Order By: Relevance
“…PAX6 is a member of the PAX gene family and acts as a key regulator in the development of the eyes, central nervous system and pancreas (15,32,33). Furthermore, it has been demonstrated that PAX6 serves an oncogenic role in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…PAX6 is a member of the PAX gene family and acts as a key regulator in the development of the eyes, central nervous system and pancreas (15,32,33). Furthermore, it has been demonstrated that PAX6 serves an oncogenic role in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Pax6 is expressed throughout the forebrain from early developmental stages onward and has been implicated in multiple processes, including forebrain patterning, FMB positioning, boundary formation, and axonogenesis (14). At the time of thalamus induction, the posterior border of Pax6 expression precisely marks the FMB.…”
Section: Discussionmentioning
confidence: 99%
“…4I) (31). Previously Pax6 has been implicated in axonogenesis in the forebrain (11,14,28,32,33), prompting us to investigate whether the ectopically induced cTh neurons in the midbrain form thalamus-like projections. GFP electroporations into the tectum led to only a few posterior projections joining the lateral longitudinal fascicle, whereas ectopic cTh neurons induced by coexpression of Pax6 and SmoM2 in the midbrain formed abnormal projections growing in different directions depending on the specific location of their cell bodies in the tectum (Fig.…”
Section: Repressor Function Of Irx3 Mediates Competence For Thalamus mentioning
confidence: 99%
See 1 more Smart Citation
“…The transcription factor Pax6 is highly conserved among vertebrates and is essential for a wide variety of developmental processes within the central nervous system (CNS), sensory organs, and the endocrine system [15][16][17][18][19]. Homozygous Pax6 mutant mice (Pax6…”
Section: Introductionmentioning
confidence: 99%